2021–2022 Florida Citrus Production Guide: Exocortis, Cachexia, and Other Viroids - Amit Levy; Ozgur Batuman; Ronald H. Brlansky (EDIS, 2021)
Reviewed March 2021. There are no changes in recommendation from 2020.